LOCAL ELECTIONIN POLITICAL PHILOSOPHY PERSPECTIVE AND ITS RELEVANCY TOWARD THE IMPROVEMENT OF POLITICAL DEMOCRACY AT THE LOCAL LEVEL (LOCAL ELECTION CASE STUDY OGAN ILIR REGENCY IN 2010) - Abun, A Rifai (Istinbath, 2015)
This research entitled: Local electionin Political Philosophy Perspective and Its Relevancy toward the Improvement of Political Democracy at The Local Level(Local election Case Study OganIlirRegency in 2010). Local election Ogan Ilir Regency which took place on June 5, 2010, based on law No.12 of 2008, was a manifestation of political democracy at the local level, which required the participation of local communities. Local electionOganIlirRegency in 2010 followed by 4 pairs of candidates, and won by incumbent candidate number 4 (Ir. Mawardi Yahya and Drs. H. Daud Hasyim), got criticism and caused various demos from the societies. The emergence of cases of fraud in the local election Ogan Ilir Regency was as interpreted by the elite political parties and local communities as a liberal democracy, not as electoral.  It was obvious that local election used as a means power struggle to become a predator and power-hungry head area, which in practice justified any means, and the local election was also interpreted as a democratic party and made the object of material benefits for local communities. In this context, the local election was worthy and deserved to be studied from the political perspective, which initiated the order of life together and reviewed, parsed the nature and norms of political democracy deeply, for realizingof head regional and government which had good governance. The data in this research was taken by field observation, interview and literature study.  Analysis data used the approach of historical, hermeneutic and heuristics methods.